Can you sleep at night? Capturing absurd snippets of the everday world through illustration - Lee, Jia Zhen (Nanyang Technological University, 2020)
Morals are our ideological beliefs that we play out in everyday life, standards we essentially live our lives by. They are also the principles that help guide our behaviour, enabling us to live cooperatively in groups. Often, we hold on too tightly to these values thinking that they shape us and would help us discern the good from the bad. However, if we were to take a closer look back, we are actually all not that very good. While we all try to keep up with the projection of a certain kind of image of ourselves every day, there are times when we slip and our flawed and ugly side comes creeping out.